(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
the article focuses on the study of methods of literary education in foreign countries, scientists who studied them, types of methods of literary education abroad, practical importance of these methods of literary education, their introduction into the Uzbek educational process.